The estimation of the number of OE-chains and realizable OE-routes for cutting plans with combined contours - Makarovskikh, Tatiana; Savitsky, Egor (Yugoslav Journal of Operations Research, 2020)
Cuts combination of plane details leads to optimization of material use and shortening of cutting time. However, the problem of cutting plan realization arises. This plan has to satisfy the following restrictions: (1) part cut off a sheet does not require further cuts (constructing of OE-route); (2) there are some restrictions on placement of pierce points (constructing of PPOE-cover). In this paper we consider the problem of enumeration the OE-chains for cutting plan with combined cuts and necessary conditions of realizable cutting.